(untitled) (Società e diritti, 2018)
In this article the authors want to present some projects and researches of the international working group created to carry out a survey on the public image of the administration of justice that digital social media (social media) and social networks connected to them (face book and twitter) and to investigate how this image is perceived by citizens. The Working Group, to which the same authors take part, and which involves the universities of Milan (IT), Cordoba (AR) and San Marcos of Lima (PE) intends to analyse the media at international, national and local level, the digital ones including the cinematographic works disseminated on online platforms, starting from the premise that justice is strongly linked to politics. Key words: Administration of justice, judicial iconography, digital "social media", social networks, politics of law